Edukasi Perpajakan Bagi Perangkat Desa Jatijajar Untuk Mewujudkan Kepatuhan Pajak - Arief, Sandy; Mahmud, Amir; Susilowati, Nurdian; Sari, Puji Novita (Universitas Negeri Semarang, 2025)
The Village Law provides villages with the freedom to manage their finances independently. However, tax management and compliance with tax provisions still face challenges. Many village officials, especially village treasurers, do not yet understand the correct tax procedures, such as determining taxable objects and proper calculations. The purpose of this service is to provide education and training on understanding taxation, especially VAT, Income Tax, and correct tax calculation practices. The methods used are socialization, training, and mentoring targeting the Jatijajar Village officials, Bergas District, Semarang Regency. The results of the service show that 75% of village officials have been able to calculate taxes in accordance with applicable provisions. From this, there is an increase in tax accuracy and compliance, as well as more reliable and relevant village financial reports. It is recommended that further mentoring be carried out regarding tax reporting and preparation of SPT so that village officials can carry out tax obligations more efficiently and on time.